Scientific attitude analysis on students in class XI natural science regarding human blood circulation system material - Dwy Santi; Risma Delima Harahap; Sakinah Ubudiyah Siregar (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Attitude is a tendency to behave and may be viewed as an individual's response to a stimulus. Although attitudes toward biology, particularly the human circulatory system, can be represented by the acceptance or rejection of certain biological objects. This research aims to determine high school students' attitudes at SMA Negeri 2 Bilah Hulu towards biology subjects, particularly the material on the human circulatory system. This research employed a qualitative strategy and descriptive approaches. The findings of this survey indicate that the indicator of pleasure in studying biology is 78.30%, the indication of curiosity is 82.92%, the indicator of interest in extending biology time is 80.90%, and the indicator of interest in a career in biology is 79.89%. This research concludes that students have the highest positive attitude toward the indicator of curiosity, while they have the least positive attitude toward the indicator of enjoyment in learning biology. Good curiosity from students is a good foundation in the learning process; it's just that innovative learning activities that are more interactive are needed if you want students to be more interested in learning biology.Abstrak Sikap ialah kecenderungan dalam berprilaku dan dapat diartikan sebagai ungkapan seseorang terhadap suatu stimulus. Sedangkan sikap terhadap biologi khususnya mata pelajaran sistem peredaran darah manusia dapat diungkapkan melalui perasaan/perilaku menerima atau menolak terhadap objek biologi tersebut. Adapun tujuan dari penelitian ini yaitu untuk mengetahui sikap peserta didik terhadap mata pelajaran biologi khususnya pada materi sistem peredaran darah manusia pada tingkatan sekolah menengan atas lebih tepatnya di SMA Negeri 2 Bilah Hulu. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode deskriptif. Hasil dari penelitian ini yaitu pada indikator kesenangan dalam belajar biologi dengan persentase sebesar 78.30%, indikator rasa ingin tahu dengan persentase sebesar 82.92%, kemudian pada indikator ketertarikan memperbanyak waktu biologi dengan persentase sebesar 80.90%, dan pada indikator ketertarikan berkarir dibidang biologi dengan persentase sebesar 79.89%. Adapun kesimpulan dari penelitian ini yaitu bahwa sikap positif peserta didik paling banyak pada indikator rasa ingin tahu, sedangkan sikap positif peserta didik paling rendah ada pada indikator kesenangan dalam belajar biologi. Rasa ingin tahu yang baik dari peserta didik adalah pondasi yang bagus dalam proses pembelajaran, hanya saja diperlukan inovasi kegiatan belajar yang lebih interaktif jika ingin peserta didik menjadi lebih tertarik untuk belajar biologi.